Modality - Royes, Sònia Roca (Cambridge elements. Elements in metaphysics,, 2023)
This volume guides the reader into the topic of modality, with especial emphasis on the most recent debates. The first part is devoted to modality as a general phenomenon, and the second part is focused on metaphysical modality.